1999
DOI: 10.1073/pnas.96.1.238
|View full text |Cite
|
Sign up to set email alerts
|

Toward a cancer therapy with boron-rich oligomeric phosphate diesters that target the cell nucleus

Abstract: The viability of boron neutron capture therapy depends on the development of tumor-targeting agents that contain large numbers of boron-10 ( 10 B) atoms and are readily taken up by cells. Here we report on the selective uptake of homogeneous f luorescein-labeled nido-carboranyl oligomeric phosphate diesters (nido-OPDs) by the cell nucleus and their long-term retention after their delivery into the cytoplasm of TC7 cells by microinjection. All nido-OPDs accumulated in the cell nucleus within 2 h after microinje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 14 publications
1
20
0
Order By: Relevance
“…33 10 12 atoms/cell, respectively. From this result, we confirmed that these liposomes can deliver sufficient amount of boron 10 8 -10 9 10 B atoms/tumor cell to B16 melanoma cells for effective BNCT 33 .…”
Section: In Vitro Release Of Polyborane From Liposomessupporting
confidence: 66%
“…33 10 12 atoms/cell, respectively. From this result, we confirmed that these liposomes can deliver sufficient amount of boron 10 8 -10 9 10 B atoms/tumor cell to B16 melanoma cells for effective BNCT 33 .…”
Section: In Vitro Release Of Polyborane From Liposomessupporting
confidence: 66%
“…Other nuclear-targeting molecules are nido-carboranyl oligomeric phosphate diesters. Despite their multiple negative charges, oligomeric phosphate diesters have been shown to target the nuclei of TC7 cells following microinjection (69), suggesting that the combination of oligomeric phosphate diesters with a celltargeting molecule capable of crossing the plasma membrane could provide both selectivity and nuclear binding. Such a conjugate recently has been designed and synthesized (70), although its biological evaluation has yet to be reported.…”
Section: Low Molecular Weight Agentsmentioning
confidence: 99%
“…Other nuclear-targeting molecules are nido-carboranyl oligomeric phosphate diesters (OPDs). Despite their multiple negative charges, OPDs have been shown to target the nuclei of TC7 cells following microinjection (74), suggesting that the combination of OPDs with a cell-targeting molecule capable of crossing the plasma membrane could provide both selectivity and nuclear binding. Such a conjugate has been designed and synthesized (75), although its biological evaluation has yet to be reported.…”
Section: Biochemical Precursors and Dna Binding Agentsmentioning
confidence: 99%